2008
DOI: 10.1016/j.watres.2007.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A clay–vesicle system for water purification from organic pollutants

Abstract: Vesicle-clay complexes in which positively charged vesicles composed of didodecyldimethylammonium bromide (DDAB) were adsorbed on montmorillonite removed efficiently anionic (sulfentrazone, imazaquin) and neutral (alachlor, atrazine) pollutants from water. These complexes (0.5% w:w) removed 92-100% of sulfentrazone, imazaquin and alachlor and 60% of atrazine from a solution containing 10mg/L of it. A synergistic effect on the adsorption of atrazine was observed when all pollutants were present simultaneously (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 28 publications
(34 reference statements)
2
33
0
Order By: Relevance
“…Their results indicated that 87-99 % of the pollutants were removed from aqueous phase. Similar results were also obtained by Undabeytia et al (2008). Furthermore, Polubesova et al (2006) used micelles of BDMHDA preadsorbed on montmorillonite to remove TC and sulfonamide antibiotics from water and found that the micelle-clay complexes (1 % w/w) removed 96-99.9 % of antibiotics from their water solutions.…”
Section: Influence Of Colloids On the Environmental Behaviors Of Pcs supporting
confidence: 71%
“…Their results indicated that 87-99 % of the pollutants were removed from aqueous phase. Similar results were also obtained by Undabeytia et al (2008). Furthermore, Polubesova et al (2006) used micelles of BDMHDA preadsorbed on montmorillonite to remove TC and sulfonamide antibiotics from water and found that the micelle-clay complexes (1 % w/w) removed 96-99.9 % of antibiotics from their water solutions.…”
Section: Influence Of Colloids On the Environmental Behaviors Of Pcs supporting
confidence: 71%
“…This scale was selected for easy handling of the solution, rapid separation of organoclay, and rapid temperature setting which were essential to obtain informative results with minimizing experimental errors. formation and structures of organoclays [18,19,22]. The modification with DDAB was also confirmed based on a broad absorbance (νN-H: ~3400 cm -1 ) and sharp peaks (νC-H:…”
Section: Removal Of and Degradation Of β-Lactam Antibioticsmentioning
confidence: 68%
“…The organoclay can be readily prepared by mixing appropriate surfactants and clay minerals in the aqueous media [17][18][19]. Hydrophobic organic pollutants in water are incorporated into surfactant aggregates formed between the layers of clay minerals [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Surface Science Society of Japan (http://www.sssj.org/ejssnt)chains without specific functional groups [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%